Effects of Different Heat Treatments on the Structure and Physicochemical Properties of Proteins from Skimmed Camel’s Milk - WANG Tao, WANG Danlin, HE Jing, JI Rimutu (Shipin Kexue)
In this study, we investigated the changes of physicochemical properties and structure of defatted camel’s milk proteins with four different heat treatments (65 ℃/30 min (T1), 85 ℃/15 s (T2), 120 ℃/15 s (T3), and 135 ℃/5 s (T4)) by measuring particle size, potential, turbidity, secondary structure, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) pattern, tertiary structure, surface hydrophobicity, free sulfhydryl group and disulfide bond content. The results showed that the particle size of camel’s milk proteins increased, the absolute value of the zeta potential decreased, and the turbidity increased with increasing temperature. Heat treatment had a significant effect on the secondary and tertiary structures, resulting in a decrease in the relative contents of α-helix and β-turn and an increase in the relative contents of β-fold and random coil in camel’s milk proteins. T3 had the greatest effect on the particle size, zeta potential, secondary structure and tertiary structure compared with the unheated control. SDS-PAGE profiles showed that the intensities of the soluble whey protein bands gradually decreased as the heating temperature increased. Observations by laser scanning confocal microscopy (LSCM) showed that the heat treatment caused protein aggregation, and T3 and T4 resulted in the production of large protein polymers. Under the T1 and T2 conditions, protein polymers were formed mainly through disulfide bonding. However, with the increase in heating temperature, the disulfide bonds of camel’s milk proteins were broken under the T3 and T4 conditions, resulting in the formation of free sulfhydryl groups and the exposure of the hydrophobic groups of camel’s milk proteins. The above results indicated that the structural and physicochemical properties of camel’s milk proteins can be changed to different degrees by different heat treatments, which in turn can affect the stability of camel milk. The results of this study provide a theoretical reference for the development of liquid camel’s milk products.